Piloting the Climate Security Sensitiveness Scoring Tool (CSST) A case study assessing the climate security sensitiveness of Climate-Smart Villages (CSV) in Nyando, Kenya - Sarzana, Carolina; Melgar, Adriana; Läderach, Peter R.D.; Pacillo, Grazia (2022)
This report aims to pilot the Climate Security Sensitiveness Tool (CSST) on an existing climate adaptation intervention package: the Climate Smart Village (CSV) approach implemented in Nyando, Kenya. This report provides the theoretical and conceptual background underlying the CSST, it provides introductory information on the case study through describing the characteristics of the Nyando basin and of the CSV approach. It then proceeds on testing the CSST on this case study with the goal of providing recommendations for improving the conflict-sensitiveness and peace responsiveness of this climate action program.